Integrating Human Resource Development Systems in Tourism Vocational Education Institutions - Dameria Girsang; Ivan Benedict Tambunan; Lyandru Togu Mulia Tambunan; Susanna Silvia Sembiring (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This research is driven by the suboptimal human resource management in tourism vocational education in meeting dynamic industry demands, especially in graduate competency alignment, educator capacity, certification implementation, and industry partnership quality. This study aims to describe the practice of human resource management in tourism vocational education, analyze competency development strategies of students and educators, identify obstacles to human resource management, and formulate a development model that is more relevant to the needs of the tourism sector. This study uses a qualitative case study design in Indonesian tourism vocational education institutions, with data collected through semi-structured interviews, limited observations, and document analysis involving institutional leaders, educators, staff, students, alumni, and industry partners, and analyzed using reflexive thematic analysis to identify key patterns of institutional experiences and practices. The results identify four key findings, including a mismatch between graduate competencies and industry needs, underdeveloped educator capacity building, limited substantive industry partnerships, and fragmented human resource management, while the quality of training and certification programs remains uneven. These findings indicate the need for a more integrative, adaptive, and collaborative human resource management system in tourism vocational education to improve relevance and competitiveness.